The genomic and transcriptional landscape of primary central nervous system lymphoma - Josefine Radke; Naveed Ishaque; Randi Koll; Zuguang Gu; Elisa Schumann; Lina Sieverling; Sebastian Uhrig; Daniel Hübschmann; Umut H. Toprak; Cristina López; Xavier Pastor Hostench; Simone Borgoni; et al. (Nature Communications, 2022)
Primary lymphomas of the central nervous system (PCNSL) are defined as diffuse large B-cell lymphomas (DLBCL) confined to the CNS. Here, the authors complete whole genome sequencing and RNA-seq to characterize 51 PCNSLs, and find common mutations in immune pathways and upregulated TERT expression and find distinct pathway differences between DLBCL and other primary CNS lymphomas.